2009
DOI: 10.1073/pnas.0909589106
|View full text |Cite
|
Sign up to set email alerts
|

Structure of an integrin αIIbβ3 transmembrane-cytoplasmic heterocomplex provides insight into integrin activation

Abstract: Heterodimeric integrin adhesion receptors regulate diverse biological processes including angiogenesis, thrombosis and wound healing. The transmembrane-cytoplasmic domains (TMCDs) of integrins play a critical role in controlling activation of these receptors via an inside-out signaling mechanism, but the precise structural basis remains elusive. Here, we present the solution structure of integrin ␣IIb␤3 TMCD heterodimer, which reveals a righthanded coiled-coil conformation with 2 helices intertwined throughout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
179
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 146 publications
(187 citation statements)
references
References 41 publications
7
179
0
1
Order By: Relevance
“…S1) that have been shown to interact with the Nterminal a IIb CT MP region in a NMR structure of membraneanchored a IIb CT peptide (Vinogradova et al, 2000). This interaction might be important in keeping the resting integrin state, but the same interaction was not found in the NMR structure of the a IIb b 3 TM-CT heterodimer determined in organic solvent (Yang et al, 2009) (Fig. 1C).…”
Section: Icam-1 Binding (Nomalized Mfi)mentioning
confidence: 76%
See 1 more Smart Citation
“…S1) that have been shown to interact with the Nterminal a IIb CT MP region in a NMR structure of membraneanchored a IIb CT peptide (Vinogradova et al, 2000). This interaction might be important in keeping the resting integrin state, but the same interaction was not found in the NMR structure of the a IIb b 3 TM-CT heterodimer determined in organic solvent (Yang et al, 2009) (Fig. 1C).…”
Section: Icam-1 Binding (Nomalized Mfi)mentioning
confidence: 76%
“…1A) and by NMR using the isolated peptides either in lipid bicelles (Fig. 1B) or in organic solvent (Yang et al, 2009) (Fig. 1C).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported on the interaction of the talin-1 FERM domain and the β3 CT with micelles and phospholipid vesicles (15,27,(38)(39)(40). Here, we studied these interactions using a β3 CT construct tethered to phospholipid bilayers to understand the energetics of the overall process.…”
Section: Discussionmentioning
confidence: 99%
“…inside-out signaling (Dai et al, 2015;Ginsberg et al, 2005). The activation states of integrins are tightly controlled by interactions between α-and β-subunits at both the membrane-proximal cytoplasmic tails (CTs) and the transmembrane domains (Vinogradova et al, 2002;Yang et al, 2009;Zhu et al, 2009). Integrin conformational changes toward active states can be triggered by the binding of cytoplasmic integrin activators to the integrin β CTs (Liu et al, 2000;Ma et al, 2007;Moser et al, 2009b;Qin et al, 2004).…”
Section: Introductionmentioning
confidence: 99%